ASSESSMENT OF THE PHYSICOCHEMICAL SUITABILITY OF OILS AND FRYING FATS RESIDUALS FOR BIODIESEL PRODUCTION - Rubia Pina Luchetti Camargo; Aysha Jussara Ivonilde Carrim; Pedro Ivo Brandão e Melo Franco; Nelson Roberto Antoniosi Filho (Diponegoro University, 2016)
Frying food is a quick and tasty way of cooking, but generate a large amount of residual frying oils and fat (RFOF). However, these residuals can be used for making soap, animal food, and biodiesel. Companies have been increasingly interested in developping green solutions to waste management that control its generation, collection, recycling, and disposal. With the increase of biodiesel demand, RFOFs are increasingly used to produce biofuel instead of soap. However, unwanted residuals of RFOFs need to be cleaned and their physical-chemical characteristics need to be analyzed before they can be used for biodiesel production. RFOF was submitted to a Liquid-Liquid Extraction (LLE) to remove highly oxidized compounds and short-chain free fatty acids. Here, we evaluated the physicochemical characteristics and filtered RFOFs to remove waste to improve biodiesel production. We found that that the liquid-liquid extraction (LLE) and filtration using adsorbent decrease first-order oxidized compounds, like hydroxy-dienone, and decrease water content. Those are key parameters to assess quality of raw material for biodiesel production.